DISSECTING ROBERT GLEAVE'S ORIENTALIST UNDERSTANDING - Evalinda, Evalinda; Rasyid, Daud; Rasyid, Aisyah Daud; Hayatuddin, Hayatuddin (Moderation | Journal of Islamic Studies Review, 2025)
This article examines the thoughts and approaches of Robert Gleave in the study of Islamic law, focusing on criticizing his methodology and epistemology. As an orientalist, Gleave adopts a philological and historical approach in researching Islamic law, especially in the Shia tradition. This approach has been criticized by various Muslim scholars for ignoring the normative and transcendental aspects of Islamic law. Moreover, Gleave's skepticism towards classical sources of Islamic law raises questions regarding the validity of his approach in understanding Islamic law as a revelation-based system. The paper also discusses Gleave's bias in interpreting Islamic hermeneutics as well as the limitations of his analysis in applying Islamic law in the context of contemporary Muslim life. Using the perspective of Islamic epistemology, this paper concludes that Gleave's approach needs to be examined more critically so that it is not only Western academically oriented but also respects the principles of Islamic law held by Muslims.